Prelude to Power The Parisian Radical Press, 1789-1791 - Censer, Jack Richard (Johns Hopkins University Press, 2019)
Otiginally published in 1976. This investigation focuses on the ideology of the radical press during the French Revolution. Events, individuals, and institutions were important, but they were reported in such a manner as to make them subordinate to ideas. In their descriptions of the people and institutions of the Revolution, radicals drew heavily on the stereotypes provided by their ideology. The author analyzes the radicals of 1789 to 1791 with respect to collective interests and concerns. For these radicals, ideology governed from 1789 through 1791. And, insofar as events had any impact on the radicals, occurrences of 1790 were important because they coincided with radical shifts in opinion. Subsequent and more famous events came too late to have much impact on radical views. The author reveals that Jacobin thought of 1792 and 1793 had definite origins dating from 1789. The similarity between radical thought and the ideology of Robespierre proves that Jacobinism was not a hasty doctrine of the moment but the direct product of positions assumed since 1789.